ANALYSIS CAPACITY OF SUNGAI TATAS AND SUNGAI BELASUNG IN BANJARMASIN CITY USING HEC-RAS SOFTWARE - Putri, Shefa Calista; Nashrullah, Eddy; Novitasari, Novitasari (CERUCUK, 2026)
Tatas River and Belasung River, which have four sluice gates, have experienced a reduction in cross-sectional area and riverbed sedimentation. Therefore, an analysis of the river's cross-sectional capacity is necessary to assess the ability to accommodate the designed flood discharge. In this study, the analyses conducted include hydrological and hydraulic analysis. Hydrological analysis includes frequency analysis and plan flood discharge analysis. Hydraulic analysis uses 1D Unsteady Flow simulation in HEC-RAS software. Based on the research results, the design flood discharge values for return periods of 2, 5, 10, and 25 years are 1.63 m³/s, 2.05 m³/s, 2.35 m³/s, and 2.75 m³/s for the Tatas River, and 1.48 m³/s, 1.86 m³/s, 2.13 m³/s, and 2.49 m³/s for the Belasung River. The simulation results show that the cross-sectional capacity of the Tatas River and Belasung River is insufficient to accommodate the design discharge at all return periods. Keywords: Cross-sectional Capacity, Tatas River, Belasung River, HEC-RAS, Sluice Gate